Manufacturing Planning and Control for Supply Chain Management (The Mcgraw-Hill/Irwin Series Operations and Decision Sciences) - Jacobs F. Robert (Mc Graw-Hill, 2010)
Manufacturing Planning & Control for Supply Chain Management, 6e by Jacobs, Berry, and Whybark (formerly Vollmann, Berry, Whybark, Jacobs) is a comprehensive reference covering both basic and advanced concepts and applications for students and practicing professionals. The text provides an understanding of supply chain planning and control techniques with topics including purchasing, manufacturing, warehouse, and logistics systems. Manufacturing Planning & Control for Supply Chain Management, 6e continues to be organized in a flexible format, with the basic coverage in chapters 1-8 followed by the last four chapters that focus on the integration of manufacturing with the supply chain. Each chapter provides a managerial issues overview, a detailed technical presentation related to the topic, company examples, and concluding principles. This book is the essential desk reference for Supply Chain Planning and Control techniques.